Assessment of Spatio-Temporal Changes of Land Use in Tangail Municipality Using GIS - Mamun, SA; Runa, HA; Hoque, MMM; Sheikh, S; Arif, RH (Journal of Environmental Science and Natural Resources, 2019)
Tangail district has undergone dramatic changes in its physical form through urbanization. Here, agricultural land and vegetation cover have been transformed into built-up areas; fallow land and water bodies into reclaimed built-up areas. The aim of this research was to develop land use and land cover (LULC) maps of the Tangail Municipality area in 2001, 2011 and 2017. Landsat (TM) Satellite images of the year 2001, 2011, and 2017 were used. On-screen digitization method was applied to prepare the final maps with four classes (water bodies, vegetation, agricultural land, and settlement area) of land use. The study reveals that the settlement area was increasing over the study period, and mainly agricultural land and water body were converted into settlement. It was found that about 48.73% areas were covered with the settlement area in 2017. Similarly, a substantial increase was seen in the areas of vegetation as about 824.49 ha land added to this category throughout the study years. In contrast, the agricultural land (786.30 ha) and water body (114.73 ha) were declined between 2001 and 2017. J. Environ. Sci. & Natural Resources, 11(1-2): 245-252 2018